Community-Associated Methicillin-Resistant Staphylococcus aureus Necrotizing Pneumonia without Evidence of Antecedent Viral Upper Respiratory Infection. Issue 3 (2014) - Toro, Cristina Moran; Janvier, Jack; Zhang, Kunyan; Fonseca, Kevin; Gregson, Dan; Church, Deirdre; Laupland, Kevin; Rabin, Harvey; Elsayed, Sameer; Conly, John
Abstract : BACKGROUND: USA300 community-associated (CA) methicillin-resistant Staphylococcus aureus (MRSA) strains causing necrotizing pneumonia have been reported in association with antecedent viral upper respiratory tract infections (URI). METHODS: A case series of necrotizing pneumonia presenting as a primary or coprimary infection, secondary to CA-MRSA without evidence of antecedent viral URI, is presented. Cases were identified through the infectious diseases consultation service records. Clinical and radiographic data were collected by chart review and electronic records. MRSA strains were isolated from sputum, bronchoalveolar lavage, pleural fluid or blood cultures and confirmed using standard laboratory procedures. MRSA strains were characterized by susceptibility testing, pulsed-field gel electrophoresis, spa typing, agr typing and multilocus sequence typing. Testing for respiratory viruses was performed by appropriate serological testing of banked sera, or nucleic acid testing of nasopharyngeal or bronchoalveloar lavage specimens. RESULTS: Ten patients who presented or copresented with CA necrotizing pneumonia secondary to CA-MRSA from April 2004 to October 2011 were identified. The median length of stay was 22.5 days. Mortality was 20.0%. Classical risk factors for CA-MRSA were identified in seven of 10 (70.0%) cases. Chest tube placement occurred in seven of 10 patients with empyema. None of the patients had historical evidence of antecedent URI. In eight of 10 patients, serological or nucleic acid testing testing revealed no evidence of acute viral coinfection. Eight strains were CMRSA-10 (USA300). The remaining two strains were a USA300 genetically related strain and a USA1100 strain. CONCLUSION: Pneumonia secondary to CA-MRSA can occur in the absence of an antecedent URI. Infections due to CA-MRSA are associated with significant morbidity and mortality. Clinicians need to have an awareness of this clinical entity, particularly in patients who are in risk groups that predispose to exposure to this bacterium.